Modelo de inventarío aplicado a la industria farmacéutica - Macías Olvera, Iván (2010)
The objective of this study is to find the optimal inventory level in the pharmaceutical industry by using both math simulation and combinatorial optimization. Data used for this study were provided by the planning department. This department played an important role to execute this project. Finally, it was possible to define an inventory policy that the company should apply by making some changes to the current policy.